PENERAPAN VICARIOUS LIABILITY DALAM TINDAK PIDANA KORUPSI TERKAIT DENGAN DISKRESI PENYELENGGARAAN ADMINISITRASI PEMERINTAHAN - Zulfa, Eva Achjani; Ismail, Audaraziq (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
Discretion is used as a solution to deal with the problem of the principle of legality in terms of governance that is not regulated by law. On the other hand, discretion is relevant to corruption where the actions of state officials and corrupt government will hinder the achievement of state goals. Therefore, it is necessary to identify who is responsible for the misuse of discretion. In this article, we will discuss the implementation of vicarious liability in corruption related to the administration of regional government administration in order to effectively impose criminal sanctions on corruptors in the misuse of discretion in the context of administering government administration. Keywords: Criminal Liability, Corporations, Government Institutions